Pembinaan Kesadaran Hukum Peserta Didik melalui Metode Pembelajaran Role-Playing di Kelas VII SMP Negeri 5 Garut - Tira Cantika; Syfa Kaila Damayanti; Ulpa Dwi Martiani Martiani; Valerie Nadya Stien; Tetep Tetep (PTK: Jurnal Tindakan Kelas, 2025)
The urgency of this research is based on the low legal awareness among junior high school students, which is reflected in the still rampant violations of school rules and low understanding of legal norms. The purpose of this study is to increase the legal awareness of students in class VII-H of SMP Negeri 5 Garut. The method used is through role-playing on the material "Complying with Norms". This study uses the Kurt Lewin Classroom Action Research (CAR) design which is implemented in 2 (two) cycles. Learning refers to the role-playing Teaching Module, and is supported by research instruments including observation sheets, interview guidelines, field notes, and student reflections. The results of the study showed a significant increase in student involvement, understanding, and attitudes towards legal norms from cycle I to cycle II. Modifications to actions in cycle II, such as the application of the think-pair-share strategy and the preparation of more contextual scenarios. The conclusion of the study confirms that the role-playing method can foster legal awareness more effectively than conventional methods, as well as encourage the internalization of legal values in students' daily behavior.